Profiling Gene Programs in the Blood During Liver Regeneration in Living Liver Donors. Issue 10 (10th September 2019) - Lawrence, Michael C.; Darden, Carly M.; Vasu, Srividya; Kumano, Kenjiro; Gu, Jinghua; Wang, Xuan; Chan, Jinyan; Xu, Zhaohui; Lemoine, Benjamin F.; Nguyen, Phuong; Smitherman, Cynthia; Naziruddin, Bashoo; et al.
Abstract : The human liver's capacity to rapidly regenerate to a full‐sized functional organ after resection has allowed successful outcomes for living donor liver transplantation (LDLT) procedures. However, the ability to detect and track physiological changes occurring during liver regeneration after resection and throughout the restoration process is still lacking. We performed a comprehensive whole‐transcriptome RNA sequencing analysis of liver and circulating blood tissue from 12 healthy LDLT donors to define biomarker signatures for monitoring physiological activities during liver regeneration at 14 time points for up to a 1‐year procedural follow‐up. LDLT donor liver tissue differentially expressed 1238 coding and noncoding genes after resection, and an additional 1260 genes were selectively regulated after LDLT. A total of 15, 011 RNA transcript species were identified in the blood in response to liver resection. The transcripts most highly regulated were sequentially expressed within 3 distinct peaks that correlated with sets of functional genes involved in the induction of liver resection–specific innate immune response (peak 1), activation of the complement system (peak 2), and platelet activation and erythropoiesis (peak 3). Each peak corresponded with progressive phases of extracellular matrix degradation, remodeling, and organization during liver restoration. These processes could be tracked by distinct molecular signatures of up‐regulated and down‐regulated gene profiles in the blood during phases of liver repair and regeneration. In conclusion, the results establish temporal and dynamic transcriptional patterns of gene expression following surgical liver resection that can be detected in the blood and potentially used as biomarker signatures for monitoring phases of liver regeneration.